Conflict, Displacement and Overlapping Vulnerabilities : Understanding Risk Factors for Gender-Based Violence among Displaced Women in Eastern Democratic Republic of Congo - Kelly, Jocelyn TD (World Bank, Washington, DC, 2021)
Eastern Democratic Republic of Congo has been embroiled in decades-long conflict that has resulted in the forced displacement of millions of people and extremely high rates of gender-based violence. Much attention has been focused on conflict-related sexual violence; however, it is important to recognize that intimate partner violence is one of the most pervasive forms of gender-based violence in the world, including in conflict settings. This paper is among the first to use a large, randomized survey to analyze both sexual violence and intimate partner violence as outcomes. Displacement increases a woman’s risk of past-year intimate partner violence by 6 percent and experiencing war abuses increases the risk of lifetime intimate partner violence by 9 percent, after adjusting for other risk factors. Both exposure to war-related experiences and displacement independently increase the risk of past-year sexual violence by 6 percent, after adjusting for other risk factors. Forced displacement and traumatic war-related experiences are risk factors for intimate partner violence and sexual violence in this setting. Acknowledging these risks and creating programs that explicitly address the high risk of violence faced by displaced and war-affected women can more effectively break the cycles of violence that are often perpetuated in fragile settings.